[P173] Proposal of a comprehensive pre-treatment QA procedure in IMRT/VMAT techniques. (August 2018) - Alhazmi, Abdulaziz; Gianoli, Chiara; Martins, Juliana; Neppl, Sebastian; Veloza, Stella; Reiner, Michael; Belka, Claus; Parodi, Katia
Abstract : Purpose: The abstract aims to propose a comprehensive pre-treatment QA procedure, independent of TPS calculation and Linac control system, to detect errors related to dose calculation and/or dose delivery in state-of-art IMRT/VMAT techniques. Methods: The proposed pre-treatment QA procedure consists of the subsequent application of two independent methodologies: one relevant to dose calculation QA and the other to dose delivery QA. The dose calculation QA relies on validating the analytical TPS dose distribution with a more accurate equipment-specific Monte-Carlo (MC) dose simulation[1] . A Geant4 (MC) model is developed to be used for 3D dose distribution simulations. The dose delivery QA relies on an in-house developed, plan-specific, 3D non-transit dosimetry approach based on EPID technology. The methodology reconstructs a 3D dose distribution in a virtual cylindrical water phantom based on calibrated and back-projected EPID images[2] . The accuracy of the reconstructed 3D dose distribution has been investigated in this work. The sensitivity to geometric and dosimetric errors between the original treatment plan and intentionally modified treatment plans has been assessed in terms of controlled translational shifts of the MLC, rotational shifts of the gantry and over-dosages. Quantification is based on gamma evaluation with acceptance criteria of (3 mm, 3%). The QA evaluation of the dose calculation is performed between the TPS dose distribution and the MC dose simulation. Afterwards, the dose delivery QA evaluation is performed between the TPS calculation and the reconstructed 3D dose distribution in the virtual water phantom, as sufficiently accurate in homogeneous (water) media. Results: The initial adequacy of the two presented methodologies for the proposal of a comprehensive pre-treatment QA procedure is promising. An overview of the results under controlled changes and/or errors will be presented and the interpretation of detected errors in real clinical scenarios will be discussed. Conclusions: The proposed comprehensive pre-treatment QA procedure provides independent validation methods with the potential to quantitatively support the decision making process in presence of errors related to dose calculation or dose delivery.